2018
DOI: 10.1002/kin.21184
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and quantification of the electrophilic reactivities of substituted thiophenes and structure‐reactivity relationships

Abstract: Second-order rate constants (k 1 ) have been measured spectrophotometrically for reactions of 2-methoxy-3-X-5-nitrothiophene 1a-c (X = NO 2 , CN, and COCH 3 ) with secondary cyclic amines (pyrrolidine 2a, piperidine 2b, and morpholine 2c) in CH 3 CN and 91:9 (v/v) CH 3 OH/CH 3 CN at 20 • C. The experimental data show that the rate constants (k 1 ) values exhibit good correlation with the parameters of nucphilicity (N) of the amines 2a-c and are consistent with the Mayr's relationship log k (20 • C) = s(E + N).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…It is interesting to note that the slopes close to unity (1.02 and 1.08) obtained in this work indicates that equation (1) is applicable to these reactions 7‐10,15‐19 . According to equations (3) and (4), the electrophilicity parameter E values of −8.46 and −9.52 are thus obtained for benzofurazans 1 and 2 , respectively.…”
Section: Resultssupporting
confidence: 70%
“…It is interesting to note that the slopes close to unity (1.02 and 1.08) obtained in this work indicates that equation (1) is applicable to these reactions 7‐10,15‐19 . According to equations (3) and (4), the electrophilicity parameter E values of −8.46 and −9.52 are thus obtained for benzofurazans 1 and 2 , respectively.…”
Section: Resultssupporting
confidence: 70%
“…When the relation k −1 ≪ k 2 + k 3 [NuH] 0 is satisfied, Equation is rewritten as Equation , suggesting that the formation of the intermediate zwitterion ZH is the rate‐limiting step of the uncatalyzed reaction: k obsd =k1[] NuH 0…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the agreement between calculated and experimental rate constants is remarkably good because Eq. (1) usually predicts rate constants of polar organic reactions within a factor of 10–100 . Follet and co‐workers have shown that Eq.…”
Section: Resultsmentioning
confidence: 99%
“…(1) usually predicts rate constants of polar organic reactions within a factor of 10-100. [16,21,35,[44][45][46][47][48][49][50][51][52][53][54] Follet and co-workers [46] have shown that Eq. (1) predicts the rate constants for reactions of indol-3-ylmethylium ions with various phosphines and pyridines in dichloromethane solutions at 20°C within a factor of 0.33-87.2.…”
Section: Comparison Of Predictions Rate Constants With Experimental Rmentioning
confidence: 99%